2021
DOI: 10.3390/cancers13215295
|View full text |Cite
|
Sign up to set email alerts
|

Cure the Incurable? Recent Breakthroughs in Immune Checkpoint Blockade for Hepatocellular Carcinoma

Abstract: HCC usually arises from a chronic inflammation background, driven by several factors including fatty liver, HBV/HCV viral infection and metabolic syndrome. Systemic treatment for advanced HCC remains disappointing due to its strong resistance to chemotherapy and even to tyrosine kinase inhibitors (TKIs). Recently, the use of ICI therapy has revolutionized the systemic treatment of advanced HCC. For the first time, clinical trials testing ICIs, anti-CTLA-4 and anti-PD1/PDL1 reported a survival benefit in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…Recently, a meta-analysis indicated that patients with high PD-L1 expression (>1% score) had longer survival than patients with <1% PD-L1 expression. Therefore, the PD-L1 status may be a potential predictive biomarker in the context of anti-PD-1/PD-L1 therapy (98). Moreover, one study showed that HCC patients with Wnt/CTNNB1 mutations were insensitive to anti-PD-1/ PD-L1 therapy and had a worse prognosis than patients without mutations (113).…”
Section: Potential Biomarkers Of Clinical Response In Combination The...mentioning
confidence: 99%
“…Recently, a meta-analysis indicated that patients with high PD-L1 expression (>1% score) had longer survival than patients with <1% PD-L1 expression. Therefore, the PD-L1 status may be a potential predictive biomarker in the context of anti-PD-1/PD-L1 therapy (98). Moreover, one study showed that HCC patients with Wnt/CTNNB1 mutations were insensitive to anti-PD-1/ PD-L1 therapy and had a worse prognosis than patients without mutations (113).…”
Section: Potential Biomarkers Of Clinical Response In Combination The...mentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is one of the most malignant tumours in the world and also a severe worldwide health threat [1, 2]. Because of the difficulty of diagnosis, the majority of HCC patients are already at an advanced stage when they are diagnosed, and their median survival time is <1 year [3–5]. However, if HCC patients at treated at an early stage, the 5 year survival rate can increase to ~70 % [6].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, more and more researchers have proved that the combination therapy of gene therapy and chemotherapy shows a synergistic therapeutic effect for HCC [ [18] , [19] , [20] , [21] , [22] ]. PD-1 (programmed cell death protein 1) or PDL-1 (programmed cell death 1 ligand 1) combined with sorafenib has been used for the treatment of HCC and achieved a good synergistic therapeutic effect [ [23] , [24] , [25] , [26] ]. It is expected to be a powerful therapeutic method in clinical application.…”
Section: Introductionmentioning
confidence: 99%